Synthesis and Evaluation of 6‐Ethoxy‐2‐mercaptobenzothiazole Scaffolds as Potential α‐Glucosidase Inhibitors. Issue 26 (8th July 2022) - Mojibade Balogun, Modinat; Shamim, Shahbaz; Mohammed Khan, Khalid; Mahdavi, Mohammad; Salar, Uzma; Adebayo Oladosu, Ibrahim; Mohammadi‐Khanaposhtani, Maryam; Ali Faramarzi, Mohammad; Olufunke Moronkola, Dorcas; Taha, Muhammad; Rahim, Fazal; Perveen, Shahnaz
Abstract: 6‐Ethoxy‐2‐mercapto benzothiazole derivatives 1 –26 were synthesized by following two different reaction schemes. Products 1 –18 were synthesized by treating 6‐ethoxy‐2‐mercaptobenzothiazole with different phenacyl bromides whereas compounds 19 –26 were prepared by the reaction of 6‐ethoxy‐2‐mercaptobenzothiazole with benzyl bromide derivatives under basic conditions. Structural characterization of compounds was performed by mass spectrometric and NMR spectroscopic techniques. Spectroscopic data was well supported to confirm the structures of each analog. All synthetic compounds were subjected to check their potential to inhibit the α ‐glucosidase enzyme. All scaffolds demonstrated potent inhibitory activity (IC50 =60.1±3.6–319.7±7.5 μ M) than standard acarbose (IC50 =750.0±10.5 μ M). Compounds 18 (IC50 =60.1±3.6 μ M) and 26 (IC50 =77.0±4.4 μ M) having another electron‐rich heterocyclic ring system were identified as the two top‐most potent compounds of the series. Kinetic studies ascertained the competitive type inhibition by the most potent analogs. Detailed binding interactions analyses with docking simulations were also carried out which revealed a distinct binding pattern of ligands (synthetic molecules) with the enzyme's active site. Abstract : A range of synthetic 6‐ethoxy‐2‐mercapto benzothiazoles 1 –26 were identified as potential inhibitors of α ‐glucosidase enzyme. In comparison to standard acarbose (IC50 =750.0±10.5 μ M), all molecules displayed potent inhibitory activity in the range of IC50 value from 60.1±3.6 to 319.7±7.5 μ M. Potent analogs showed competitive type inhibition, revealed by kinetic studies. The docking study demonstrated important binding interactions of ligands (synthetic molecules) with the enzyme's active site.